Compensation Audit Case at Casemix Hospital X - Yastori, Yastori; Putri, Riza Suci Ernaman; Khumaira, Nurul Fitri; Oktavia, Dewi (Universitas Muhammadiyah Sidoarjo, 2024)
Audit Compensation Audits result in operational activities and hospital financial systems becoming disrupted and unstable. Based on a preliminary survey at Hospital This research aims to analyze Compensation Audit cases carried out by health insurance providers in 2023. The type of research used is using the Mixed Method, a research approach that combines or associates qualitative and quantitative forms. This research was conducted in March - June 2024. The research population was 11 compensation audit cases in 2023. Total sampling technique. An in-depth analysis was carried out on 11 compensation audit cases based on analysis of medical resumes, related regulations and based on ICD-10 and ICD-9-CM coding rules. The results of research that carried out an in-depth analysis of compensation audit cases showed that most compensation audit cases were caused by the enforcement of treatment classes with a total of 3 cases, specific management 2 cases, combination code 1, availability of death reports 1, regulations for enforcing the main diagnosis 1, specific management for main diagnosis 1, unavailability of anatomical pathology attachments 1, errors in establishing the main diagnosis and non-compliance with medical procedures and supporting documents 1. Compensation Audit Case Solution, namely the coder must understand medical records, claim submission documents, ICD-10, ICD-9-coding rules CM, health insurance provider and hospital PPK claim regulations, doctors need to provide clear, specific management and be able to determine the patient's condition. treatment class from the start of entry and the health insurance verifier must have the same perception as the previous verifier and be careful in reading and analyzing the claim submission documents.